TORC: A virtual reality controller for in-hand high-dexterity finger interaction - Lee, Jaeyeon; Sinclair, Mike; Gonzalez Franco, Mar; Ofek, Eyal; Holz, Christian (CHI Conference on Human Factors in Computing Systems Proceedings (CHI 2019), 2019)
Recent hand-held controllers have explored a variety of haptic feedback sensations for users in virtual reality by producing both kinesthetic and cutaneous feedback from virtual objects. These controllers are grounded to the user’s hand and can only manipulate objects through arm and wrist motions, not using the dexterity of their fingers as they would in real life. In this paper, we present TORC, a rigid haptic controller that renders virtual object characteristics and behaviors such as texture and compliance. Users hold and squeeze TORC using their thumb and two fingers and interact with virtual objects by sliding their thumb on TORC’s trackpad. During the interaction, vibrotactile motors produce sensations to each finger that represent the haptic feel of squeezing, shearing or turning an object. Our evaluation showed that using TORC, participants could manipulate virtual objects moreprecisely (e.g., position and rotate objects in 3D) than when using a conventional VR controller.